Virtual crop modeling for technology impact assessment - lessons from a potato crop growth model - Kleinwechter, U.; Asseng, Senthold; Gastelo, M.; Ritchie, J.; Nelson, J. (German Institute for Agriculture in the Tropics and Subtropics, 2013)
Efforts are under way in the agricultural research for development community to employ crop growth simulation models for the ex"=ante assessment of the impacts of agricultural technologies, in particular improved crop varieties. The approach, dubbed ``virtual crop modelling'', consists in the manipulation of genetic coefficients of the cultivars contained in crop growth models to simulate productivity effects of genetic improvements brought about by future breeding efforts and assesses the impacts of these improvements under field conditions. However, the suitability of the models for this purpose is not yet proven.